Fluorescence Turn On-Off Sensing of Copper (II) Ions Utilizing Coumarin-Based Chemosensor: Experimental Study, Theoretical Calculation, Mineral and Drinking Water Analysis - Arslan, Fatma Nur; Geyik, Gonul Akin; Koran, Kenan; Ozen, Furkan; Aydin, Duygu; Elmas, Sukriye Nihan Karuk; Yilmaz, Ibrahim (Springer/Plenum Publishers, 2020)
Herein, we report the preparation of a fluorescent sensor based on coumarin derivative for copper (II) ion sensing in CH3CN/HEPES media. 6,7-dihydroxy-3-(4-(trifluoro)methylphenyl)coumarin (HMAC) sensor was fabricated and analyzed by spectroscopic techniques. The sensor demonstrates turn on-off fluorescence quenching in the presence of copper (II) ions at 458 nm. A clear complex between the chemosensor HMAC and copper (II) ions was characterized by ESI-MS as well as the Job's method. Also, the limit of detection (LOD, 3 sigma/k) value was determined as 24.5 nM in CH3CN/HEPES (95/5, v/v) buffer media (pH = 7.0). This value is lower than the admissible level of copper (II) ions in drinking water (maximum 31.5 mu M) reported by EU Water Framework Directive (WFD) and World Health Organization (WHO) guidelines. The theoretical calculations (density functional theory, DFT) have been performed for the geometric optimized structures. As a final stage, real sample analyses have successfully been performed by using HMAC, as well as ICP-OES method. The relative standard deviation for copper (II) in mineral and drinking water samples has been determined to be below 0.15% and recovery values are in the range of 95.48-109.20%.
Keywords: Fluorescence sensor; Copper; Coumarin; Drinking water; Mineral water; DFT